Isolation and Characterization of Biooxidizing Bacteria from the Obuasi Gold Mining Site - Asmah, R.H. (University of Ghana, 1998)
Processing of gold arsenopyrite and sulphide ores is currently done with biooxidizing bacteria. This procedure is preferred because of its environmental friendliness and efficiency of gold recovery from ores, compared to the conventional methods. The efficiency of biomining is, however, largely influenced by the origin of biooxidizing bacteria used and local organisms have been found to be better adapted to extracting gold from the ore from which they were isolated. The work reported in this thesis was conducted with the objective of isolating and characterizing local acidophilic bioleaching bacteria from surface arsenopyrite and underground sulphide gold ores and underground mine water at the Ashanti Goldfields Company (AGC) in Ghana, one of the world’s richest gold mines. Biooxidizing bacteria were also isolated from slurry from the commercial bioleaching tank at AGC and characterized for comparative purposes. Local biooxidizing bacteria were isolated from surface arsenopyrite and underground sulphide gold ores and underground mine water and identified using cultural, physiological, morphological and biochemical criteria. In all, eleven bacterial isolates were obtained from the samples collected. Their cell morphology showed that seven isolates were straight rods while the others were curved rods. All the bacterial isolates were physiologically either ferrous iron (Fe2+) oxidizers or sulpho (S0) - oxidizers, Gram negative, mesophiles as well as aerobes. Three representative pure biooxidizing bacteria isolates were obtained from the surface ore (SO). These were, S01-Fe2+ and S02-Fe2+ both of which were ferrous iron oxidizers and S03-S0 which was a sulpho oxidizer. Similarly, three pure isolates were obtained from the underground ore (UOl- Fe2+, U02-Fe2+ and U03-S0). However, only two representative ferrous iron oxidizers were purified rom underground mine water (UWl-Fe2+ and UW2-Fe2+). The ferrous iron bacterial isolate 2 (S02- Fe2+, U02-Fe2+ and UW2-Fe2+) from each of the samples failed to grow on solid media whilst, the ferrous isolate l (S01-Fe2+, U01-Fe2+. UWl-Fe2+) as well as the sulpho oxidizers (S03-S0 and U03 - S°) grew on solid media. Biooxidizing bacterial isolates (BT1-Fe2+, BT2-Fe2+and BT3-S0) obtained from the commercial bioleaching tanks exhibited similar characteristics. Characterization of the purified bacterial isolates using cultural, physiological, morphological and biochemical criteria revealed that the ferrous iron oxidizers, isolate 1 (BT1-Fe2+, S01-Fe2+, U01-Fe2+ and UWl-Fe2+) were T. ferrooxidans and the second isolates (BT2-Fe2+, S02-Fe2+, U02-Fe2+ and UW2-Fe2+) were L. ferrooxidans. The sulpho oxidizers (BT3-S0, S03-S0 and U03-S0) were identified as T. thiooxidans. In addition to the absence of sulpho-oxidizing bacterium (T. thiooxidans) in the underground mine water, the iron oxidation rates of T. ferrooxidans and L. ferrooxidans isolates obtained from the sample were slower compared to isolates of the same bacteria from the other samples. Furthermore, T. ferrooxidans isolated from underground mine water did not exhibit pleomorphism and had a unique colony size (2-5mm) as compared to the other isolates (0.5-5mm) thus suggesting that it could be of a different strain. Attempts to characterize the bacterial isolates and detect strain differences by restriction fragment length polymorphism of their DNA, however, proved difficult because of smearing of bands. Soluble proteins from crude bacterial cell lysates of all the purified isolates (BT1-Fe2+, S01-Fe2+, U01-Fe2+, UWl-Fe2+, BT3-S0, S03-S0, U03-S0, BT2-Fe2+, S02-Fe2+, U02-Fe2+, UW2-Fe2+) were electrophoresed on 15-20 % acrylamide gradient gels, using the SDS-tris-glycine discontinuous buffer system, and the protein profiles analyzed. This electrophoretic analysis showed that the T. ferrooxidans isolates (BT1-Fe2+, S01-Fe2+, U01-Fe2+ and UWl-Fe2+) had similar protein profiles. Similarly, T. thiooxidans isolates (BT3-S0, S03-S0 and U03-S0) and L. ferrooxidans isolates (BT2- Fe2+, S02-Fe2+ and U02-Fe2+) had unique protein profiles. The protein profiles clearly differentiated the bacterial isolates at the species level. This study has therefore demostrated the presence of local isolates of the 3 important biooxidizing bacteria utilized in biomining and appears to suggest that some of the local isolates are different strains that may be used for more effficent gold extraction at the AGC.